A Survey of English Majors’ Writing Ability Based on China’s Standards of English Language Ability - Yue, Xuan (Journal of Educational Research and Policies, 2026)
China’s Standards of English Language Ability (hereinafter referred to as CSE) was officially released in 2018, marking the first English proficiency assessment standard specifically tailored for English learners in China and ushering in a new phase in the development of China’s English proficiency assessment system. This study investigates the English writing abilities of English major students based on the summary table and sub-item descriptions of written expression ability in the CSE, employing a combination of qualitative and quantitative research methods. The aim is to assist teachers in formulating appropriate teaching objectives and designing effective teaching content, thereby improving students’ English writing proficiency. The results indicate that the written expression ability of English major students falls between Levels 4 and 5 as defined in the CSE. Students demonstrates their strongest performance in written description, while written argumentation appears to be their relatively weakest area. Based on these findings, this study aims to provide beneficial insights for English writing instruction.